Terminal Bus Kuantan Singingi Dengan Pendekatan Struktur Sebagai Elemen Estetika - Saputro, Aris; Hidayat, Wahyu; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Kuantan Singingi is a city district that has a fairly dense population with population data from 2010-2015 experiencing an increase of 0.013 per year. Kuantan Singingi Regency has the potential to develop a terminal if it functions according to the needs of the community by providing transportation in and out of the province and therefore the City of Taluk Kuantan should have a terminal that facilitates the need for (AKDP) and floats a stopover at the Inter-City Transport Terminal Province (AKAP) which crosses the city of Taluk Kuantan. Research methods used through field surveys, literature reviews and documentation. Kuantan Singingi Terminal is designed with the theme Structure As Aesthetic Elements applied to column and beam structures that apply the characteristic of Ornamentation Structure. The concept used is taken from the formation of the vehicle's engine, namely the Machine Gear. The results of this design are focused on the circulation system that directs and does not confuse the user. Keywords: Bus Terminal, Structure as Aesthetic Element, Kuantan Singingi.